Addressing missed opportunities for cervical cancer screening in Nigeria: a nursing workforce approach - Okolie, EA; Aluga, D; Anjorin, S; Ike, FN; Ani, EM; Nwadike, BI (ecancer, 2022)
Cervical cancer is the commonest gynaecological cancer affecting women, especially in low and middle-income countries (LMICs). Despite the availability of evidence on multiple prevention pathways, including vaccination and screening, the cervical cancer burden continues to increase, especially in LMICs. This disease typifies health inequality as more than 85% of related morbidity and mortality occur among women of low socio-economic status residing in developing countries. In Nigeria, cervical cancer is the second leading cause of cancer morbidity and mortality. Sadly, Nigeria lacks a tailored cervical cancer control policy or population-based screening programme which is recommended. Consequently, existing screening services are opportunistic, sparsely distributed and have reached less than 9% of eligible Nigerian women. This article highlights the current status of cervical cancer screening in Nigeria, contextualises the role of female nurses and proffers novel approaches to address missed opportunities for screening by leveraging the nursing workforce.